Cost-effectiveness of pertussis booster vaccination in the Netherlands. - Rozenbaum, M; De Cao, E; Postma, M (2012)
The aim of the current study is to estimate the epidemiological and economical consequences of several extended pertussis booster vaccination strategies and to explore the impact of parameters surrounded by large uncertainty on the cost-effectiveness. We developed an age structured transmission dynamic model to evaluate the impact of programs targeting (i) adolescents or adults using a single booster dose, (ii) a combination of adolescent and adult vaccination, and (iii) an every 10 years booster dose. The base case analysis, that is a single adolescent booster administered at the age of 12 years, resulted in a reduction of pertussis infections. However, due to an increase in the number of symptomatic infections in adults, the benefits in terms of QALYs gained and costs saved in children were partly offset. Despite these negative indirect effects in the adult population, administering an additional booster dose could still be considered cost effective with an ICER of €4200 per QALY gained. Combining an adolescent booster dose at the age of 10 (most cost-effective age for a single adolescent booster dose) with an adult (18-30 years) booster dose always resulted in favorable ICERs (<€10,000/QALY). Finally the every 10 year booster dose resulted in an ICER of €16,900 per QALY. The impact of different assumptions regarding the disease epidemiology, disease-related parameters, and vaccination program-related issues was limited. To conclude, we show that extended pertussis booster vaccination strategies are likely to be considered as cost-effective.